Reactive transport in porous media for CO2 sequestration: pore scale modelling using the Lattice Boltzmann method - Gao, Jinfang; Xing, Huilin; Tian, Zhiwei; Pearce, Julie K.; Sedek, Mohamed; Golding, Suzanne D.; Rudolph, Victor (Computers & Geosciences, 2016)
Injection of CO subsurface may lead to chemical reactivity of rock where CO is dissolved in groundwater. This process can modify pore networks to increase or decrease porosity through mineral dissolution and precipitation. A lattice Boltzmann (LB) based computational model study on the pore scale reactive transport in three dimensional heterogeneous porous media (sandstone consisting of both reactive and non-reactive minerals) is described. This study examines how fluid transport in porous materials subject to reactive conditions is affected by unsteady state local reactions and unstable dissolution fronts. The reaction of a calcite cemented core sub-plug from the Hutton Sandstone of the Surat Basin, Australia, is used as a study case. In particular, the work studies the interaction of acidic fluid (an aqueous solution with an elevated concentration of carbonic acid) with reactive (e.g. calcite) and assumed non-reactive (e.g. quartz) mineral surfaces, mineral dissolution and mass transfer, and resultant porosity change. The proposed model is implemented in our custom LBM code and suitable for studies of multiple mineral reactions with disparate reaction rates. A model for carbonic acid reaction with calcite cemented sandstone in the CO-water-rock system is verified through laboratory experimental data including micro-CT characterization before and after core reaction at reservoir conditions. The experimentally validated model shows: (1) the dissolution of calcite cement forms conductive channels at the pore scale, and enables the generation of pore throats and connectivity; (2) the model is able to simulate the reaction process until the reaction equilibrium status is achieved (around 1440 days); (3) calcite constituting a volume of around 9.6% of the whole core volume is dissolved and porosity is consequently increased from 1.1% to 10.7% on reaching equilibrium; (4) more than a third of the calcite (constituting 7.4% of the total core volume) is unaffected, which suggests that this calcite is not connected with open pores (at the resolution of the model) that the acidic fluid can access. The model enables exploration of the porosity change in systems as they react, which has applications for analysis of the induced permeability change at the macroscale.